PENGARUH TINGKAT PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP INFORMATION ASYMMETRY DENGAN VARIABEL KONTROL FIRM SIZE DAN EARNING QUALITY PADA PERUSAHAAN TERBUKA DI INDONESIA - Devina Andriani Tandiono; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
This study aimed to examine and to prove the affect of corporate social responsibility disclosure level on information asymmetry. Corporate social responsibility disclosure was measured by Corporate Social Responsibility Disclosure Level that valued by GRI criteria. Information asymmetry measured by bid-ask spread. This research used firm size and earning quality as control variables. This research was carried out on public companies in Indonesia which published sustainability report with a sample of 104 observations. The result showed that there was a positive significant correlation of corporate social responsibility disclosure on bid-ask spread. The result also showed that firm size had no affect on bid-ask spread, while the earning quality had negative significant correlation on bid-ask spread.